Narsisisme dan Kompleks Oedipus yang Tergambar dalam Pygmalion, Karya George Bernard Shaw - Syam, Essy; Fauzi, Mohd.; Syamsidar, Raja (JURNAL PUSTAKA BUDAYA, 2017)
AbstractThis writing analyzes narcisism and oedipuis complex as refelcted in a literary work entitles âpygmalionâ written by George Bernard Shaw. Thus, the objective of this analysis is to show and to analyze how narcisism and Oedipus complex are suffered from the protagonist of this work. To reach that objective, this analysis applies psychoanalitical analysisÂ  to demonstrate the mental condition of the main character. Related to that idea, this analysis applies adescriptive analysis method in which the result of the analysis will be described clearly. From teh presented description, it will show how the main character of this work lives his life and in his interaction with other characters will describe his mental condition.Â Keywords:Â Pygmalion, psychoanalisis, Narcisism, Oedipus Complex.Â Â Â AbstrakTulisan ini menganalisis kasus Narsisme dan Kompleks Oedipus yang tergambar pada sebuah karya sastra berjudul Pygmalion yang ditulis oleh GeorgeÂ  Bernard Shaw.Â  Maka tujuan penelitian ini adalah untuk memperlihatkan dan menganalisis bagaimana kasus narsisme dan kompleks oedipus yang dialami oleh tokoh utama karya ini. Untuk mencapai tujuan itu, kajian ini menerapkan kajian psikoanalisisÂ  untuk memperlihatkan kondisi kejiwaan tokoh utama yang mengalami gangguan jiwa yang dimanakan Narsisime dan Kompleks Oedipus.Â  Kajian ini menerapkan metode deskriptif analisis dimana hasil analisis akan dideskripsikan dengan jelas. Dari deskripsi yang dijabarkan akan memperlihatkan bagaimana tokoh utama karya ini dalam kehidupannya dan interaksinya dengan tokoh yang lain memperlihatkan kondisi jiwanya.Â Kata Kunci:Â Pygmalion, Psikoanalisis. Narsisime, Kompleks Oedipus